Monitoring of the online interventions in an experience of collaborative learning with future teachers of mathematics - Sgreccia, Natalia Fátima (2012)
This paper analyses the temporal distribution of the asynchronous interventions made by a group of seven trainee mathematics teachers during online collaborative work carried out for two months in mid-2011. As part of the Residence subject within the degree in training mathematics teachers at the National University of Rosario (Argentina), students have to prepare a report giving details of their experience of observing mathematics classes during first-semester courses on engineering degrees (or similar) and also correct their partners´ work. A set of weekly activities was drawn up to organise the task for the Residence subject. The space used was Google Docs, whose features include access to the history of revisions made to each document, including the date, time and person working on a particular report. We used this history of revisions to analyse students´ time management at four levels and tried to characterise the degree of systematisation in the process of developing their own work and peer correction. From the results, we can conclude that this systematisation was achieved for the group overall. But there was no correspondence between what was actually done and the set weekly activities, because the interventions were concentrated in the last two weeks of the experience. One way of improving this lack of correspondence would be to get the Residence teachers and trainee mathematics teachers together at the start of the task week to prepare the set of weekly activities.